Pengaruh Pengembangan Karir terhadap Produktivitas Pegawai melalui Motivasi di PPPPTK Bidang Otomotif dan Elektronika Malang - Cintya Khairul Ulum; Dianawati Suryaningtyas; Arien Anjar Puspitasari (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This study to determine the Effect of Career Development on Employee Productivity through Motivation at PPPPTK in the Automotive and Electronics Sector in Malang. The method in this research is an explanatory research method using quantitative research type. Population in this research is the whole of the employees in PPPPTK in Automotive and Electronics Sector Malang with 96 employees, the type and nature of the population are heterogeneous and limited. The data analysis technique used in this study is path analysis. The results of this study indicate that career development variables affect employee productivity in PPPPTK BOE Malang, career development variables affect motivation in PPPPTK BOE Malang, and motivation as a mediating variable effectively mediates the effect of career development on employee productivity..